Gambaran Sikap Ibu Hamil Tentang Pencegahan Stunting Di Wilayah Kerja Puskesmas Rambipuji - Umamah, Nurul Harirotul; Sugijati, Sugijati; Palupi, Jenie (Jember Maternal and Child Health Journal, 2024)
Introduction: stunting is a serious public health problem in Indonesia. One of the risk factors that influence stunting is pregnant women’s poor attitude towards preventing stunting. Based on the results of a preliminary study, it was found that some pregnant women did not know about stunting. The aim of the research is to determine the attitude of pregnant women regarding stunting prevention in the Rambipuji Community Health Center working area. Method: This research design is descriptive research. The sampling technique used purposive sampling of 34 pregnant women with a questionnaire as the research instrument. Data analysis uses descriptive analysis. Results: The results of the study showed that the majority of pregnant women had a good attitude towards stunting prevention, 64.7%, with the remaining 35.3% of pregnant women having a fair attitude towards stunting prevention. Discussion: Good attitudes of pregnant women towards stunting prevention involve awareness and proactive actions in maintaining health and nutrition. By paying attention to their own health and fetal development, pregnant women contribute significantly to preventing stunting in children. It is hoped that mothers’ good attitudes towards preventing stunting can be maintained and improved, thereby contributing to a reduction in stunting rates and better child health in the future.